1983
DOI: 10.1111/j.1423-0410.1983.tb03657.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Group Chimeras: A Review

Abstract: More than 70 spontaneous chimeric propositi in man are known. This review attempts to summarize the information given by 32 twin chimeras, 32 dispermic chimeras and 11 chimeras of unestablished type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…The proportion of 'foreign' or 'grafted cells' in a chimera varies from case to case. The proportion of 'foreign' cells may very well exceed that of the cells from the germ line [1], or even completely re place the germ line cells in the blood [2].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of 'foreign' or 'grafted cells' in a chimera varies from case to case. The proportion of 'foreign' cells may very well exceed that of the cells from the germ line [1], or even completely re place the germ line cells in the blood [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, none of the patients displayed congenital or acquired chimerism, 4 as evidenced by microsatellite analysis. This result was remarkable, as spontaneous chimerism had been reported to occur quite frequently.…”
Section: Discussionmentioning
confidence: 93%
“…2,13,14,51 However, varying proportions of RBC subsets of different phenotypes over time, as also observed in some of the patients of this study, are not an exclusive feature of Rh mosaicism but were also reported for hematopoietic chimerism. 4,5 Moreover, LOH is a major mechanism for inactivation of tumor-suppressor genes, and some of these genes are believed to reside on the short arm of chromosome 1, next to the RH locus. 52 Because of the aforementioned circumstances, it seems generally advisable to perform diagnostic steps to exclude hematologic disease in individuals with spontaneous blood group phenotype splitting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations